Multiple Foci in Japanese Clefts and the Growth of Semantic Representation - Seraku, Tohru (Proceedings of the Amsterdam Colloquium, 2011)
There are two types of Japanese clefts, depending on the presence of a case particle attached to a focus; multiple foci are possible only in clefts with particles. This paper proposes that this distinct behavior with respect to multiple foci emerges as a consequence of the incremental growth of semantic structure within Dynamic Syntax; multiple foci are licensed when an underspecification for each item is resolved by each case particle. From this analysis also follows the partially case-specified foci and the so-called clause-mate condition.